2010
DOI: 10.1038/sj.bjc.6605669
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein 7 alters the sensitivity to interferon-based anticancer therapy in hepatocellular carcinoma cells

Abstract: BACKGROUND: A striking efficiency of interferon (IFN)-based anticancer therapy for advanced hepatocellular carcinoma (HCC) has been reported. Because its clinical efficiency greatly depends on each patient's local response, prediction of local response is crucial. METHODS: Continuous exposure of IFN-a to parental PLC/PRF/5 cells (PLC-P) and a limiting dilution method resulted in the establishment of IFN-resistant cell clones (PLC-Rs). Microarray analyses of PLC-P and PLC-Rs identified insulin-like growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…In general, the antiviral activity of PML and PML nuclear bodies are well established (21,(36)(37)(38) (44) or epigenetic silencing of genes involved in IFN signaling (45,46). Another report showed the suppression of insulin-like growth factor-binding protein 7 (IGFBP7) in IFN-a resistant hepatocellular carcinoma (HCC) cells (47). However, the crucial mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the antiviral activity of PML and PML nuclear bodies are well established (21,(36)(37)(38) (44) or epigenetic silencing of genes involved in IFN signaling (45,46). Another report showed the suppression of insulin-like growth factor-binding protein 7 (IGFBP7) in IFN-a resistant hepatocellular carcinoma (HCC) cells (47). However, the crucial mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…30 Others have shown that short hairpin RNA directed against IGFBP7 increased resistance to interferon-a/5-fluorouracil treatment, and IGFBP7 transfection restored treatment sensitivity in HCC. 31 Intravenous recombinant IGFBP7 treatment has shown good tumour-suppressive effects in mouse models of several cancers, including glioblastoma. 28,32 The potential anticancer effects of IGFBP7 in glioma therefore warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Parental PLC/PRF/5 cells transfected with short hairpin RNA for IGFBP7 showed IFN- resistance. IGFBP7 transfection into IFN-resistant HCC cells restored IFN sensitivity [106]. These results suggested that IGFBP7 could be a novel marker to predict clinical outcome to IFN-/5-FU therapy.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 63%
“…A strong antitumor activity against HCC has been demonstrated for interferon (IFN)-based combination therapy (IFN-/ 5-FU therapy) [106][107][108][109][110][111][112][113][114][115][116]. However continuous exposure to IFN- can result in IFN-resistant HCC cells.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%